Stem Cell Oriented Exosomes Regulate Cell Proliferation in Hepatoma Carcinoma - Karima, Gul; Shin, Kyusoon; Jeong, Jaemin; Choi, Dongho; Hwang, Kyung-Gyun; Hong, Jong Wook (Biotechnology and bioprocess engineering, 2023)
Reprogrammed hepatic stem cells can generate a variety of extracellular vesicular particles including exosomes with similar therapeutic potential. However, their functional application in cancer therapy is restricted due to a poor understanding of their physical properties, anti-proliferative effects, and the underlying mechanism. Here, we explore reprogrammed stem cells that can release vesicular particles with physical properties of exosomes that can exert anti-proliferative effects by regulating cell proliferation-related genes. We obtain vesicular particles with properties of exosomes expressing CD81 and CD63 with the size distribution peak observed at 155 nm. We analyze that as compared to non-treated conditions, vesicular particles have reduced cell proliferation of Hep G2 by 93.6% after 72 h. Furthermore, we also identify that B-cell lymphoma 2 has been reduced by 89.64% and activation of caspase-3 has occurred in treated conditions via the mitochondrial pathway. Therefore, our results may highlight the potential of exosomes from hepatic stem cells to play a vital role in treating liver pathologies.